Assessment of periodontal health among patients with diabetes mellitus: a retrospective study - SHUKRI, NOR MASITAH MOHAMED; RAJASEKAR, ARVINA; BALASUBRAMANIAM, ARTHI (The journal of contemporary issues in business and government, 2020)
Periodontitis, dental caries and oral cancer are among the most common dental diseases affecting people globally. Periodontitis has been identified as the sixth complication of diabetes, in which diabetic patients are more susceptible to develop periodontal disease thrice as often as non- diabetic patients. The risk of periodontitis increases in people with poorly controlled diabetes. The aim of this study was to assess the periodontal health among patients with diabetes mellitus. This retrospective study was conducted from June 2019-March 2020 among patients with diabetes mellitus. A total of 200 patients with diabetes were enrolled. Data regarding the periodontal status of the patients were collected from their records and analysis was carried out using IBM Statistical Package for Social Science (SPSS version 23). Descriptive statistics (frequency distribution and percentage) and inferential statistics (chi-square test) were done. In the present study, out of 200 diabetic patients, 116 patients had gingivitis and 84 patients had periodontitis. Prevalence of both gingivitis and periodontitis was higher among patients within the age group of 45-54 years. Also, prevalence of both gingivitis and periodontitis was higher in males than females. Association between age and periodontal status was found to be statistically significant with the p value of 0.04. The present study showed the prevalence of gingivitis and periodontitis among diabetic patients was 58% and 42% respectively.